2013
DOI: 10.1007/s10333-013-0362-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different methods of rice (Oryza sativa. L) cultivation affecting growth parameters, soil chemical, biological, and microbiological properties, water saving, and grain yield in rice–rice system

Abstract: Field experiments were conducted at DRR farm located at ICRISAT, Patancheru, in sandy clay loam soils during four seasons, Kharif 2008, Rabi 2008-09, Kharif 2009 and Rabi 2009, to investigate plant growth parameters, water-saving potential, plant root characteristics, chemical, biological and microbial properties of the rhizosphere soil, and grain yield of rice (Oryza sativa L.) by comparing the plants grown with system of rice intensification (SRI) methods, with organic fertilization only or organic + inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Singh reported water savings in SRI and ARS over PTR in both the years, in their 2‐year study at New Delhi. Saving of water in SRI over PTR has also been documented . Among the treatments of Zn fertilization and microbial inoculations, yield improvement was more in microbial inoculation, which translated into greater water savings.…”
Section: Discussionmentioning
confidence: 96%
“…Singh reported water savings in SRI and ARS over PTR in both the years, in their 2‐year study at New Delhi. Saving of water in SRI over PTR has also been documented . Among the treatments of Zn fertilization and microbial inoculations, yield improvement was more in microbial inoculation, which translated into greater water savings.…”
Section: Discussionmentioning
confidence: 96%
“…Rice plants grown under different methods of cultivation (such as conventional, [20,21]. Gopalakrishnan et al [22] also observed an increase in the soil microbiological activity, in terms of various enzymes related to nutrient mobilization in the samples from SRI treatment, over those from the conventional method of cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Rice plants grown under different methods of cultivation (such as conventional, SRI, and DSR) with/without fertilization, exhibited differences in their physiological activities and microbial populations, as a result of the aerobic/anaerobic ecological milieu in soil bringing about changes in the quantity and forms of nutrients . Gopalakrishnan et al also observed an increase in the soil microbiological activity, in terms of various enzymes related to nutrient mobilization in the samples from SRI treatment, over those from the conventional method of cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…The root systems were healthier with SRI method (50% organic and 50% inorganic) under intermittent condition. It confirmed that SRI methods support better root growth and contributed to increase number of tillers (Gopalakrishnan et al, 2013).…”
Section: Rice Performancesmentioning
confidence: 52%
“…Previous study also showed that under SRI practice with intermittent irrigation increased the number of tillers (Stoop et al, 2002;Kalsim et al, 2007;Balai Penelitian Tanah, 2011;Gopalakrishnan et al, 2013). The greater number of tillers might be largely due to wider spacing and transplanting of young and single seedlings.…”
Section: Rice Performancesmentioning
confidence: 89%